Some sequence spaces on the Orlicz space - Haryadi haryadi (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2017)
Although, the Orlicz space is a generalization of classical Banach space , the method used in [4] to construct sequences spaces on no longer work on the Orlicz space. In this paper, we construct some sequence space in the Orlicz space such that the resulting sequences spaces is a generalization of the sequence space in . We use modular to construct the Luxemburg norm and describe some topological properties in the spaces.